Hormat Dan Kasih Dalam Pernikahan Kristen Sebuah Penelitian Eksegetikal Terhadap Efesus 5:21-33 - Joy Sopater Wasiyono (SOTIRIA (Jurnal Theologia dan Pendidikan Agama Kristen), 2022)
The Apostle Paul emphasized a key to the happiness of marriage in his epistle to the Ephesians: " Nevertheless, each individual among you also is to love his own wife even as himself, and the wife must see to it that she respects her husband." - Ephesians 5:33 (NASB). Wive need the love of her husband, otherwise husband need the respect of his wive. There is a great danger that will strike marriage if the principle of Ephesians 5:33 is not applied in marriage. Call it as the Crazy Cycle. When a wife feels unloved, she reacts in a way that her husband feels disrespectful, and when a husband feels disrespected, he reacts in a way his wife feels as unloving. It keeps turning, and their relationship can get messed up. That is why an exegetical study of Ephesians 5:21-33 was done to find the foundations of Paul's apostle's teaching on respect and love. This research embodies 6 indicators of wive who respect her husband and 9 indicators of husband who love his wive. 6 indicators of wive who respect husband are: 1) respecting the work and ideas / thoughts of the husband, 2) respecting the protection and income of the husband, 3) respecting the husband's leadership, 4) respecting the analysis and advice of the husband, 5) respecting the friendship built by the husband, 6) respecting the sexual desire of the husband. 9 indicators of husbands who love wives are: 1) the husband leads in a responsible and exemplary manner, 2) the husband is ready to sacrifice for the wife, 3) the husband as a good priest in the household, 4) the husband loves the wife as loves himself, 5) the husband is ready to accept the weaknesses of his wife, 6) husband faithful work to fulfill the living, 7) husband to give attention to wife, 8) husband priority wife, and 9) husband do not think to divorce or leave wife.